The only guide to alternative investments you'll ever need the good, the flawed, the bad, and the ugly - Swedroe, Larry E.; Kizer, Jared; ProQuest (Firm) (New York : Bloomberg Press, 2008)
"Investors are actively seeking investment options other than equities, bonds, and cash that will provide diversification and improved returns. The book offers an overview of a wide range of alternative investments, explaining what each is and how it works. The author shares his opinions on which to seriously consider and which to avoid at all costs"--Provided by publisher.
Real estate -- Inflation-protected securities -- Commodities -- International equities -- Fixed annuities -- Stable-value funds -- High-yield (junk) bonds -- Private equity (venture capital) -- Covered calls -- Socially responsible mutual funds -- Precious metals equities -- Preferred stocks -- Convertible bonds -- Emerging market bonds -- Hedge funds -- Leveraged buyouts -- Variable annuities -- Equity-indexed annuities -- Structured investment products -- Leveraged funds.
Includes bibliographical references (p. 253-261) and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Portfolio management; Asset allocation; Investment analysis; Investments; Electronic books